Simulasi Perubahan Garis Pantai Teluk Belitung Kabupaten Kepulauan Meranti Menggunakan Program Genesis - Herli Fajri; Ferry Fatnanta; Sigit Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Teluk Belitung beach is located on the outer side of Asam strait that relate directly to Malacca strait and South China sea. It causes the ocean waves directly on the shoreline that pose an enough serious problem of shoreline change along the coastline. For it, necessary to study about the shoreline changes that occur coastline. This study was conducted using GENESIS program for simulate shoreline changes that will occur within a period of 5 years, 10 years and 15 years ahead. The data used to perform simulations using GENESIS  program is coastal bathymetry, winds, waves, soil properties of coast land and ocean currents and tides data. Simulation results obtained  from the increase in value of the shoreline changes that occur in the form of accretion and erosion along coastlines. Five-years results of the simulation time showed maximum shoreline change reaches 26,1 meters, which increases the simulation time of 10-years to reach 52,1 meters and at the simulation time 15-years to reach 78 meters. Analysis results of simulation results obtained the main factors that affecting the magnitude of shoreline change is occured. The soil  properties of coastal land has a grain size and cohesion of little value, so that when the waves come to the shore will be easiliy eroded coastal cliffs and carrying granules are eroded.  Keywords: shoreline change, accretion, erosion, GENESIS